A Model of Organizational Integration, Implementation Effort, and Performance - Barki, Henri; Pinsonneault, Alain (Organization Science, 2005)
The notion of integration is central to the understanding of organizations in general as well as of contemporary phenomena such as e-commerce, virtual organizations, virtual teams, and enterprise resource planning (ERP) implementation. Yet, the concept of integration is ill-defined in the literature, and the impact of achieving high levels of integration is not well understood. The present paper addresses these issues. Drawing on the literature of several fields, this paper proposes the concept of organizational integration (OI), which is defined as the extent to which distinct and interdependent organizational components constitute a unified whole. Six types of OI are identified: two intraorganizational OI (internal-operational, internal-functional) and four interorganizational OI (external-operational-forward, external-operational-backward, external-operational-lateral, and external-functional). This paper then presents a model and develops 14 propositions to predict (1) the effort needed to implement different types of OI, (2) the impact different types of OI will have on organizational performance, and (3) how six factors (interdependence, barriers to OI, mechanisms for achieving OI, environmental turbulence, complexity reduction mechanisms, and organizational configurations) influence the relationship between OI types, implementation effort, and organizational performance. The OI framework and model are then used to develop 14 propositions for ERP implementation research and to explain the findings of recent research on integration.